Prevalence of Schistosoma bovis and Schistosoma haematobium hybrids in endemic communities in Ghana - Yvonne Ashong; Frank Twum Aboagye; Isaac Owusu-Frimpong; Samuel Nyarko; Jewelna Akorli; Linda Batsa Debrah; Samuel Armoo; Alex Yaw Debrah; Dziedzom K. de Souza; Mike Yaw Osei-Atweneboana (PLoS ONE, 2026)
Background Schistosomiasis, a debilitating parasitic disease caused by Schistosoma species, poses significant public health challenges in tropical regions, particularly in sub-Saharan Africa. There is growing evidence of species hybridization which may affect transmission dynamics, host range, and treatment resistance and hamper effective control strategies. This study investigated the prevalence and genetic diversity of Schistosoma bovis and Schistosoma haematobium hybrids in endemic communities in Ghana. Methods A cross-sectional study was conducted with urine samples collected from 840 schoolchildren in Ga South and Birim North districts. Microscopy was used for initial screening, followed by molecular characterization and sequencing to confirm species identification and detection of hybrids. Prevalence rates were calculated, and genetic analyses were performed using phylogenetic methods based on the COX 1 gene of Schistosoma bovis and Schistosoma haematobium hybrids. Results Of 840 samples analysed, 96 tested positive for S. haematobium , yielding a prevalence of 11.42% [CI 95 : 9.26–13.96]. The highest prevalence in Ga South was among 13–17-year-olds [23.27%; CI 95 : 16.52–31.77], while in Birim North, it was among 5–9-year-olds [4.82%; CI 95 : 1.96–11.75]. The highest prevalence of infection in both districts: 22.58% [95% CI: 17.53–28.60] in Ga South and 4.23% [95% CI: 2.26–7.83] in Birim North was reported in males. Molecular characterization revealed that 33.33% [32/96, CI 95 : 24.70–43.27] of the samples initially diagnosed as S. haematobium were identified to be S. bovis and 11.49% [11/96, CI 95 : 6.56–19.39] of cases were hybrids. Conclusion The findings of this study highlight the prevalence of S. bovis and S. haematobium hybrids in Ghana, emphasizing the importance of accurate diagnostics and targeted control measures. Continued surveillance and research are essential to address the emerging challenges posed by schistosomiasis in endemic regions.